2019
DOI: 10.18632/oncotarget.27239
|View full text |Cite
|
Sign up to set email alerts
|

The positivity rate of 68Gallium-PSMA-11 ligand PET/CT depends on the serum PSA-value in patients with biochemical recurrence of prostate cancer

Abstract: Background: The aim of the present study is to analyze the efficacy of 68Gallium (Ga)-PSMA-11 PET/CT for detecting and localizing recurrent prostate carcinoma (PC) in patients with different prostate-specific antigen (PSA), PSA velocity (PSAvel) and doubling time (PSAdt). Results: The PR of 68Ga-PSMA-11 PET/CT showed a positive relationship with PSA levels. Even at restaging PSA-values (PSAV) of lower than 0.2 ng/ml, PR was 41%. For PSAV of 0.2-<0.5 ng/ml the PR was 45%, 62% for PSAV of 0.5-<1.0 and 72% for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Hoffmann et al reported that patients with PSA relapse had an S shaped relation between the PSA levels before 68 Ga-PSMA PET/CT and the rate of positive findings on their 68 Ga-PSMA PET/CT scans [ 18 ]. Patients with positive sites in regional lymph nodes and bones had higher median PSA values before 68 Ga-PSMA PET/CT than those with positive sites in the prostate bed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoffmann et al reported that patients with PSA relapse had an S shaped relation between the PSA levels before 68 Ga-PSMA PET/CT and the rate of positive findings on their 68 Ga-PSMA PET/CT scans [ 18 ]. Patients with positive sites in regional lymph nodes and bones had higher median PSA values before 68 Ga-PSMA PET/CT than those with positive sites in the prostate bed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many patients with PSA relapse who have a short PSADT <3 months and cancers that have a high ISUP grade 5 progress to metastatic cancer and cancer-specific death despite salvage treatment. Compared with conventional imaging modalities such as CT and bone scans, the 68 Ga-PSMA PET/CT scan has a relatively high sensitivity, especially for patients with PSA relapse and PSA levels <2 ng/mL [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Today, the Federal Drug Administration (FDA) in the USA and many guidelines recommend that urologists and oncologists examine patients with PSA relapse with 68 Ga-PSMA PET/CT [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have con rmed a high detection rate of recurrent PCa with various PSMA-targeting radiotracers even in biochemical recurrence patients with low PSA levels, and usually exceeds mpMRI (27)(28)(29). Some studies suggest a strong correlation between PSA levels and diagnostic performance of PSMA-targeting PET tracers (27)(28)(29)(30)(31). Our small sample size cohort did not allow for such a correlation, however in a future study with a larger cohort, imaging results should be correlated with PSA levels to test whether this holds true in patients who have undergone brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have con rmed a high detection rate of recurrent PCa with various PSMA-targeting radiotracers even in biochemical recurrence patients with low PSA levels, and usually exceeds mpMRI (28)(29)(30). Some studies suggest a strong correlation between PSA levels and diagnostic performance of PSMA-targeting PET tracers (28)(29)(30)(31)(32). Our small sample size cohort did not allow for such a correlation, however in a future study with a larger cohort, imaging results should be correlated with PSA levels to test whether this holds true in patients who have undergone brachytherapy.…”
Section: Discussionmentioning
confidence: 99%